One step forward and two steps back? The '20 Principles' for questioning vulnerable witnesses and the lack of an evidence-based approach. (October 2018) - Cooper, Penny; Dando, Coral; Ormerod, Thomas; Mattison, Michelle; Marchant, Ruth; Milne, Rebecca; Bull, Ray
It is a widely held belief that questioning vulnerable witnesses is a specialist skill. In England and Wales vulnerable witness advocacy training built around '20 Principles' has been developed and is being delivered. The 20 Principles do not cite a tested theoretical framework(s) or empirical evidence in support. This paper considers whether the 20 Principles are underpinned by research evidence. It is submitted that advocacy training and the approach to questioning witnesses in the courtroom should take into account the already available research evidence. The authors make recommendations for revision of the training and for a wider review of the approach taken to the handling of witness evidence.